146k views
4 votes
which choices are equivalent to the expression below? check all that apply. rad -9 A.3i B.-3 C.irad-9 D.-rad9​

User Padu
by
5.9k points

1 Answer

5 votes

Given:

Consider the expression is:


√(-9)

To find:

The equivalent expression.

Solution:

We have,


√(-9)

It can be written as:


√(-9)=√(-1* 9)


√(-9)=√(-1)* √(9)


√(-9)=i* 3
[\because √(-1)=i]


√(-9)=3i

The expression
3i is equivalent to the given expression.

Therefore, the correct option is A.

User Ethan Coon
by
5.3k points